Putaminal petechial haemorrhage as the cause of chorea: a neuroimaging study. Issue 3 (1st September 1997) - Chang, Ming-Hong; Chiang, Hung-Ting; Lai, Ping-Hong; Sy, Chern-Guey; Lee, Susan Shin-Jung; Lo, Yeung-Yuk
Abstract : OBJECTIVES: A hyperintense putamen on either CT or MRI as a finding associated with chorea has occasionally been described and is almost always associated with non-ketotic hyperglycaemia. The cause of the hyperintensity of the striatum in these images is still controversial. Some reports have found that calcification was responsible whereas others have advocated petechial haemorrhage as the cause. The purpose of this study was to determine whether hyperintense striata are caused by petechial haemorrhage or calcification, with the sequential imaging changes. SUBJECTS AND METHODS: Five patients presenting with an acute onset of either hemichorea or generalised chorea and showed either unilateral or bilateral hyperdense striatum on the initial CT were assessed. Neuroimaging studies including sequential CT and MRI examinations and detailed biochemical tests were performed. RESULTS: Three patients had pronounced hyperglycaemia and the other two patients had no biochemical abnormalities. In all patients, the first CT scans, performed within two weeks of the onset of chorea, showed a high density over the striatum contralateral to the chorea, which diminished or disappeared two months later. T1 weighted imaging disclosed hypersignal intensities over the striatum contralateral to the chorea on admission which diminished two months later. T2 weighted imaging at two months showed hyposignal intensity changes corresponding to the area with hypersignal changes on T1 weighted images, implying haemosiderin deposition. CONCLUSION: Based on the evolution of clinical manifestations and the findings of neuroimaging, putaminal petechial haemorrhage might be a new entity causing either hemichorea or generalised chorea.